2017
DOI: 10.1063/1.5003399
|View full text |Cite
|
Sign up to set email alerts
|

The third-order structure function in two dimensions: The Rashomon effect

Abstract: We study the third-order longitudinal structure function, S 3 (r), in two-dimensional turbulence. In three dimensions, there is considerable theoretical, experimental, and numerical consensus regarding the validity of Kolmogorov's arch-famous " 4 5 th law" for S 3 (r). By contrast, in two dimensions, two disparate cascades, changed dissipation anomalies, a large-scale drag, and other factors conspire to create several versions of the S 3 (r) "law." This single quantity can vary considerably when viewed from di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 54 publications
2
8
0
Order By: Relevance
“…In particular, the success of advective structure functions to diagnose energy and enstrophy cascade rates, in anisotropic, forced 2-D turbulence with large- and small-scale dissipation expands the breadth of practical scenarios where these relations could be applied. Our results extend beyond previous studies which have shown that, in isotropic 2-D turbulence, external forcing at a specific scale does not affect third-order structure function relations within the inertial cascades (Lindborg 1999; Cerbus & Chakraborty 2017), and similar results for 3-D turbulence (Banerjee & Galtier 2016). Cerbus & Chakraborty (2017) suggested that large-scale dissipation would reduce the down-scale enstrophy cascade rate as some enstrophy will be removed by large-scale drag or hypo-viscosity.…”
Section: Utility Of New Relationssupporting
confidence: 89%
See 2 more Smart Citations
“…In particular, the success of advective structure functions to diagnose energy and enstrophy cascade rates, in anisotropic, forced 2-D turbulence with large- and small-scale dissipation expands the breadth of practical scenarios where these relations could be applied. Our results extend beyond previous studies which have shown that, in isotropic 2-D turbulence, external forcing at a specific scale does not affect third-order structure function relations within the inertial cascades (Lindborg 1999; Cerbus & Chakraborty 2017), and similar results for 3-D turbulence (Banerjee & Galtier 2016). Cerbus & Chakraborty (2017) suggested that large-scale dissipation would reduce the down-scale enstrophy cascade rate as some enstrophy will be removed by large-scale drag or hypo-viscosity.…”
Section: Utility Of New Relationssupporting
confidence: 89%
“…Our results extend beyond previous studies which have shown that, in isotropic 2-D turbulence, external forcing at a specific scale does not affect third-order structure function relations within the inertial cascades (Lindborg 1999; Cerbus & Chakraborty 2017), and similar results for 3-D turbulence (Banerjee & Galtier 2016). Cerbus & Chakraborty (2017) suggested that large-scale dissipation would reduce the down-scale enstrophy cascade rate as some enstrophy will be removed by large-scale drag or hypo-viscosity. In the present simulations, approximately 99 % of enstrophy is dissipated at small scales, and approximately 90 % of energy is dissipated at large scales (table 2).…”
Section: Utility Of New Relationssupporting
confidence: 89%
See 1 more Smart Citation
“…Here S 3 (r, t) ≡ [δ r u] 3 , δ r u ≡ [u(x + r, t) − u(x, t)] .r, and the angular brackets indicate spatial and ensemble averaging [48,49]. In the statistically steady turbulence, enstrophy flux Z k is constant in the inertial range and is equal to the enstrophy dissipation rate.…”
Section: (B) and (C)]: (I)mentioning
confidence: 99%
“…In the range of scales associated with the direct cascade we expect the following to hold over a range of scales ℓ ν ≪ |h| ≪ ℓ I (viscous scale and injection scale respectively): 8) which is indicative of a direct cascade of enstrophy (see e.g. [18]). As predicted by Eyink [32], one also expects Yaglom's law [74] for the vorticity in the inertial range ℓ ν ≪ |h| ≪ ℓ I (Yaglom originally derived this prediction for passive scalar turbulence),…”
Section: Introductionmentioning
confidence: 99%